2006
DOI: 10.1381/096089206775565159
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of Wedge and Needle Hepatic Biopsy in Open Bariatric Surgery

Abstract: Needle biopsies were as effective as wedge biopsies in assessing the degree of steatosis in morbidly obese patients. More important, the presence of subcapsular fibrosis in needle biopsies was less than in wedge biopsies, suggesting an adequate tissue sample by the less invasive technique.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
22
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(25 citation statements)
references
References 20 publications
2
22
1
Order By: Relevance
“…The discrepancy, therefore, between the shear wave velocity readings taken from the immediate subcapsular liver and that of the deeper parenchyma will result in a greater dispersion of results and hence less reliability. Interestingly, it is also well known that liver biopsies obtained from subcapsular regions in any part of the liver fail to accurately estimate the degree of fibrosis [23]. The intra-observer findings for all three operators concur with the results of the interobserver study, with measurements taken from segments 5/6 and 7/8 found to be the most reliable.…”
Section: Discussionsupporting
confidence: 77%
“…The discrepancy, therefore, between the shear wave velocity readings taken from the immediate subcapsular liver and that of the deeper parenchyma will result in a greater dispersion of results and hence less reliability. Interestingly, it is also well known that liver biopsies obtained from subcapsular regions in any part of the liver fail to accurately estimate the degree of fibrosis [23]. The intra-observer findings for all three operators concur with the results of the interobserver study, with measurements taken from segments 5/6 and 7/8 found to be the most reliable.…”
Section: Discussionsupporting
confidence: 77%
“…In the current study, 85% of the subjects were associated with NASH reported more scarcely in previous studies (14,(25)(26)(27)(28). This difference of prevalence is discussed further.…”
Section: Discussioncontrasting
confidence: 41%
“…One recent study found needle biopsies to be as effective as wedge biopsies in assessing the degree of steatosis in morbidly obese patients but that the presence of subcapsular fibrosis in needle biopsies was less than in wedge biopsies. 36 Older series report that both wedged and needle biopsy samples are appropriate for assessing the degree of fibrosis or cirrhosis. 37 Significant variability has been also observed between right and left lobe liver biopsies.…”
Section: Discussionmentioning
confidence: 99%